Discrimination by definition: are definitions of 'income' used in New Zealand statutes compatible with the state's duty to protect human rights?. Issue 2 (3rd May 2020) - Barrett, Jonathan; Marriott, Lisa
ABSTRACT: This article examines whether the social policies manifest in different statutory definitions of 'income' in New Zealand discriminate against the poor. We adopt a benchmark of fundamental human rights to assess discrimination. Specifically, we examine definitions of income under income tax, welfare, accident compensation, legal aid, and student allowance legislation. We categorise income tax, accident compensation and student allowance as 'deserving income' and welfare and legal aid as 'undeserving income'. We consider three types of receipt—cash gifts, gifts in kind, and compensation—to assess the effects of using different definitions and interpretations of income. We conclude that, although overt policy discrimination may not be manifest in definitions of income, it is present and insidious, and incompatible with the state's duty to protect human rights.